2018
DOI: 10.1038/s41598-018-24893-z
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration prompts increased activity and blood feeding by mosquitoes

Abstract: Current insights into the mosquito dehydration response rely on studies that examine specific responses but ultimately fail to provide an encompassing view of mosquito biology. Here, we examined underlying changes in the biology of mosquitoes associated with dehydration. Specifically, we show that dehydration increases blood feeding in the northern house mosquito, Culex pipiens, which was the result of both higher activity and a greater tendency to land on a host. Similar observations were noted for Aedes aegy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
144
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(148 citation statements)
references
References 80 publications
4
144
0
Order By: Relevance
“…Once landed, mosquitoes exhibit exploratory bouts during which the legs and proboscis frequently contact the skin (Jones and Pilitt, 1973;De Jong and Knols, 1995;Clements, 2013). An increasing body of literature reports the presence of receptors involved size of the meal taken (Rossignol et al, 1984;Choumet et al, 2012;Cator et al, 2013;Vantaux et al, 2015;Hagan et al, 2018). These topics, however, remain a matter of debate, due to a lack of (standardized) assays to measure mosquito behavior (Stanczyk et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Once landed, mosquitoes exhibit exploratory bouts during which the legs and proboscis frequently contact the skin (Jones and Pilitt, 1973;De Jong and Knols, 1995;Clements, 2013). An increasing body of literature reports the presence of receptors involved size of the meal taken (Rossignol et al, 1984;Choumet et al, 2012;Cator et al, 2013;Vantaux et al, 2015;Hagan et al, 2018). These topics, however, remain a matter of debate, due to a lack of (standardized) assays to measure mosquito behavior (Stanczyk et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Working with mosquitoes, Hagan et al (2018) found that blood feeding was prompted by dehydration. Although sugar and blood feeding are different behaviors and dilute nectars can contain similar or lower levels of water compared to blood, it is possible that mosquitoes use the same set of physiological cues to prompt sugar feeding under dehydrating conditions [26].…”
Section: Discussionmentioning
confidence: 99%
“…For example, fructose feeding rates can vary by season and location, which may be caused by differences in temperature and humidity [21-25]. Dryness may stimulate sugar feeding behavior as has been shown by Hagan et al (2018) for blood feeding [26]. Availability of sugar sources such as floral nectar may also affect mosquito sugar feeding rates, especially in arid climates [23, 27-29].…”
Section: Introductionmentioning
confidence: 99%
“…Trehalose transporter 1 (TRET1) that transports trehalose disaccharide from the fat body to hemolymph [53] was downregulated across the time course. Silencing trehalose transporter is shown to reduce trehalose content in hemolymph and shorten the lifespan of A. gambiae under stress conditions like desiccation and high temperature [54,55].…”
Section: Transport/vesicle Mediated Transportmentioning
confidence: 99%